2023
DOI: 10.7150/thno.83942
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells and alpha-1 antitrypsin have a strong synergy in modulating inflammation and its resolution

Abstract: Rationale: Trauma, surgery, and infection can cause severe inflammation. Both dysregulated inflammation intensity and duration can lead to significant tissue injuries, organ dysfunction, mortality, and morbidity. Anti-inflammatory drugs such as steroids and immunosuppressants can dampen inflammation intensity, but they derail inflammation resolution, compromise normal immunity, and have significant adverse effects. The natural inflammation regulator mesenchymal stromal cells (MSCs) have high therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 196 publications
0
1
0
Order By: Relevance
“… 9 , 10 Numerous clinical studies have shown that MSCs regulate inflammation and promote tissue healing. 11 The migration of MSCs to the site of tissue injury can induce the secretion of a diverse range of growth factors, including epidermal growth factor, angiopoietin-1, fibroblast growth factor, platelet-derived growth factor, transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor (VEGF), hepatocyte growth factor, insulin growth factor-1 and so on, thereby facilitating tissue repair. 12–15 By activating paracrine trophic factors, endothelial cells can manufacture extracellular matrix, enhancing endothelial barrier function, and inhibiting leukocyte-endothelial cell interactions to facilitate tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Numerous clinical studies have shown that MSCs regulate inflammation and promote tissue healing. 11 The migration of MSCs to the site of tissue injury can induce the secretion of a diverse range of growth factors, including epidermal growth factor, angiopoietin-1, fibroblast growth factor, platelet-derived growth factor, transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor (VEGF), hepatocyte growth factor, insulin growth factor-1 and so on, thereby facilitating tissue repair. 12–15 By activating paracrine trophic factors, endothelial cells can manufacture extracellular matrix, enhancing endothelial barrier function, and inhibiting leukocyte-endothelial cell interactions to facilitate tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%